(3GdJbjjO aj GdMOjKs - (3GHf ofbWI GdMfHdj GdHZOGOj , eMeO Hf YHO GdZfj Hf CHj HcQ Hf TLGY, eYjf GdOjf, GHf ofbWI , CHh HcQ J (B629 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO ajg bhdg bGd QShd Gddg Udi Gddg Ydjg hSde ef GfXQ eYSQkG Ch hVY dg CXdg Gddg jhe GdbjGeI JMJ Xd YQTI jhe dGXd EdG XdI GdMOjK MQa GdPGd s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg hGdhGRY GdPi jJbOe hjbOe hjDNQ hhRYJ GdLjT s
(3HgG fXGe GdJYbjHIs
(3jHOC ef MQa GdPGd Edi HGH GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B179s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3eJaQbGJs